2012
DOI: 10.3153/jfscom.2012026
|View full text |Cite
|
Sign up to set email alerts
|

The potential inhibitory effects of the commercial diets on protease activities of Dentex dentex larvae and live foods

Abstract: The aim of this study was to determine the potential inhibitory effects of commercial diets on protease activities of Dentex dentex larvae and live foods. The highest and lowest protease activity of larvae was 387.08 ±0.23 U/mg protein and 54.66 ±0.15 U/mg protein, respectively. The highest and lowest protease activities of live foods were found in Artemia metanaupli (414.5 ±0.41 U/mg protein) and rotifer (156.25 ±0.09 U/mg protein), respectively. The significant differences between inhibition amounts of comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 18 publications
4
7
0
Order By: Relevance
“…Cahu and Zambonino Infante [6] indicated that the survival and growth of marine fish larvae solely fed on microdiet are very poor, but supplementation with live foods usually results in a marked improvement. Results of this study along with those of Diken et al [23] and Naz and Yúfera [19] showed that the contributions of Artemia metanauplii on protease activities of larvae were high, while the contributions of rotifer (B. plicatilis) and Artemia nauplii were low. Yúfera et al [39] reported that during feeding gilthead seabream larvae, the contribution of rotifer on protease activity of larval intestines was not significant, thus supporting the situation of rotifer contributions in protease activities of meagre larvae.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Cahu and Zambonino Infante [6] indicated that the survival and growth of marine fish larvae solely fed on microdiet are very poor, but supplementation with live foods usually results in a marked improvement. Results of this study along with those of Diken et al [23] and Naz and Yúfera [19] showed that the contributions of Artemia metanauplii on protease activities of larvae were high, while the contributions of rotifer (B. plicatilis) and Artemia nauplii were low. Yúfera et al [39] reported that during feeding gilthead seabream larvae, the contribution of rotifer on protease activity of larval intestines was not significant, thus supporting the situation of rotifer contributions in protease activities of meagre larvae.…”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, Artemia nauplii protease activity level was similar to Haközü [20] and Diken et al [22]. Artemia metanauplii's protease activity level was lower than Diken et al [22], higher than Haközü [20] and Diken et al [23], and similar to Naz and Yúfera [19]. The differences between the protease activity of enriched rotifer and Artemia metanauplii and also between Artemia nauplii and Artemia metanauplii [18] agree with the results obtained in this study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Enzymatic differences in live foods and the fact that Artemia is a feed source due to environmental and seasonal effects and that the copepod culture has not been achieved at industrial level despite its superiority in nutrient and enzyme activities is in the problems of live food nutrition [15][16][17][18][19][20][21][22][23]. Live foods especially in Artemia, it has been reported that the external enzymes in Artemia help larval digestion or activate existing zymogens in the larval gut [24][25][26].…”
Section: Introductionmentioning
confidence: 99%